1986
DOI: 10.5951/jresematheduc.17.1.0049
|View full text |Cite
|
Sign up to set email alerts
|

Parent Attitudes and Student Career Interests in Junior High School

Abstract: Data were collected on the mathematics achievement, spatial visualization ability, student attitudes, sex, parent attitudes, and student career interests of 1982 seventh and eighth graders from 13 midwestern junior high schools. Parent attitudes and student career interests were significant predictors of mathematics achievement over and above the other variables. Sex was the only variable that did not make a unique contribution to the variance. Three canonical variates were identified between student attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The influence of parents on children's career behavior has been well documented in the career development research (Leung, Wright, & Foster, 1987;McNair & Brown, 1983;Palmer & Cochran, 1988). For example, Pedersen, Elmore, and Dorothy (1986) reported that parental support and high aspirations for their children were instrumental factors in students' desires to pursue math/science-related careers. Studies of college students who decided to major in engineering or technology fields have supported these results (Eisler & Iverson, 1986;Hankin, 1986).…”
mentioning
confidence: 99%
“…The influence of parents on children's career behavior has been well documented in the career development research (Leung, Wright, & Foster, 1987;McNair & Brown, 1983;Palmer & Cochran, 1988). For example, Pedersen, Elmore, and Dorothy (1986) reported that parental support and high aspirations for their children were instrumental factors in students' desires to pursue math/science-related careers. Studies of college students who decided to major in engineering or technology fields have supported these results (Eisler & Iverson, 1986;Hankin, 1986).…”
mentioning
confidence: 99%